2017
DOI: 10.1016/j.psychres.2017.03.040
|View full text |Cite
|
Sign up to set email alerts
|

Intensified emotion perception in depression: Differences in physiological arousal and subjective perceptions

Abstract: People suffering from depression perceive themselves and their surroundings as more negative than healthy ones. An explanation might be that depressed individuals experience negative information as more stressful than non-depressed subjects and, consequently, respond in an amplified manner on a subjective and physiological level. To test this proposition, we presented 41 patients with recurrent depressive episodes and 42 controls with stimuli from the International Affective Picture System split into three val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 52 publications
2
19
0
Order By: Relevance
“…These biological changes are associated with other physiological parameters, which can be measured by cardiovascular responses such as increased heart rate (HR), blood pressure (BP), respiratory frequency and a change in skin conductance levels as a response to negative emotions or normal cardiovascular responses in response to positive or neutral emotional states (Barak 2006;Guo, Mrug, and Knight 2017). Wenzler et al (2017) tested 41 patients with recurrent depressive disorder and assessed their heart rate variability (HRV), galvanic skin response (GSR), skin temperature (TEMP) and respiratory frequency (RF). The research data revealed an increased TEMP (because of an elevated GSR) and RF in depressed patients compared to those in the controls (Wenzler et al 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…These biological changes are associated with other physiological parameters, which can be measured by cardiovascular responses such as increased heart rate (HR), blood pressure (BP), respiratory frequency and a change in skin conductance levels as a response to negative emotions or normal cardiovascular responses in response to positive or neutral emotional states (Barak 2006;Guo, Mrug, and Knight 2017). Wenzler et al (2017) tested 41 patients with recurrent depressive disorder and assessed their heart rate variability (HRV), galvanic skin response (GSR), skin temperature (TEMP) and respiratory frequency (RF). The research data revealed an increased TEMP (because of an elevated GSR) and RF in depressed patients compared to those in the controls (Wenzler et al 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Wenzler et al (2017) tested 41 patients with recurrent depressive disorder and assessed their heart rate variability (HRV), galvanic skin response (GSR), skin temperature (TEMP) and respiratory frequency (RF). The research data revealed an increased TEMP (because of an elevated GSR) and RF in depressed patients compared to those in the controls (Wenzler et al 2017). In another recent study, Ironson et al (2018) examined the association between positive emotional well-being and an inflammatory biomarker, C-reactive protein (CRP), which is associated with cardiovascular disorders, obesity, type II diabetes, depression and posttraumatic stress disorder.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Despite the wealth of literature on anxiety and depression, there is no consensus about how they modulate autonomic reactivity to the arousal and valence dimensions of emotional stimulation. In anxiety, there is evidence of both autonomic hyperreactivity (Schwerdtfeger, 2006) and hyporeactivity (Naveteur et al, 1987) to emotion, while depression has been either associated with greater reactivity to unpleasant stimuli (Wenzler et al., 2017), a lower reactivity to pleasant ones (Bylsma et al., 2008) or with a blunt reactivity to emotional content (Rottenberg et al., 2005). Hence, the modulation of autonomic responses to emotional dimensions by sub‐clinical and clinical anxiety and depression symptomatology remains to be characterized.…”
Section: Introductionmentioning
confidence: 99%
“…The latter objective is related to the ‘negative bias’ or propensity of depressed people to perceive everyday life situations and surrounding environments as worse and more stressful than they are. 18…”
Section: Methodsmentioning
confidence: 99%